2006
DOI: 10.1007/s00431-006-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute otitis media and respiratory viruses

Abstract: The present study was performed to elucidate the clinical outcome, and etiology of acute otitis media (AOM) in children based on virologic and bacteriologic tests. The study group consisted of 120 children aged 6 to 144 months with AOM. Middle ear fluid (MEF) was tested for viral pathogens by reverse transcriptase polymerase chain reaction (RT-PCR) and for bacteria by gram-staining and culture. Clinical response was assessed on day 2 to 4, 11 to 13, 26 to 28. Respiratory viruses were isolated in 39 patients (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 19 publications
0
58
0
1
Order By: Relevance
“…However, the highest RSV viral load occurred in winter months. Some studies have identified RSV as the most common virus in middle ear fluid samples (8,19), and RSV is frequently detected as a middle ear pathogen in the absence of AOM bacterial pathogens (22). Our finding that high RSV load in the presence of S. pneumoniae is associated with increased risk of AOM suggests that RSV detection methods that quantify viral load will help identify subjects at the highest risk of AOM.…”
Section: Discussionmentioning
confidence: 59%
“…However, the highest RSV viral load occurred in winter months. Some studies have identified RSV as the most common virus in middle ear fluid samples (8,19), and RSV is frequently detected as a middle ear pathogen in the absence of AOM bacterial pathogens (22). Our finding that high RSV load in the presence of S. pneumoniae is associated with increased risk of AOM suggests that RSV detection methods that quantify viral load will help identify subjects at the highest risk of AOM.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, influenza A virus increased permeability of polarized airway epithelial cells by inducing cytotoxic effects, whereas RSV had no effect on either R T or ZO-1 distribution. These studies provide insight into a new mechanism by which RV may predispose the host to secondary bacterial infection, as occurs in otitis media (1,12) and exacerbations of COPD (4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 97%
“…RVs are single-stranded RNA viruses responsible for the majority of upper respiratory tract infections and their complications, including otitis media, sinusitis, and bronchitis. By a sensitive detection method (polymerase chain reaction), RV was detected in 25.6% of viral-induced acute otitis media (1), and up to one-half of all viral-associated COPD and CF exacerbations (4)(5)(6)(7)9). In each of these conditions, coinfection of RV and bacteria are thought to play an important pathogenetic role.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed 71 fulltext articles, of which 12 were included (Supplemental Fig 3). 12,18,21,30,[35][36][37][38]41,[43][44] …”
Section: Aommentioning
confidence: 99%